BRAND EXPERIENCE, BRAND COMMITMENT, DAN BRAND LOYALTY PENGGUNA APPLE IPHONE DI SURABAYA - Hatane Semuel; Reynaldi Susanto Putra (Jurnal Manajemen Pemasaran, 2018)
The development of technology in the era of globalization more rapidly, that causing high competition between companies. Smartphone companies generally strive to maintain survival, gain optimal profit and strengthen the brand in the minds of consumers. To achieve these objectives then the products produced company must be useful, quality and innovative. This research objective to analyze the impact of brand experience – commitment to brand loyalty to Apple IPhone users in Surabaya. This study was carried out by distributing questionnaires to 100 respondents on Apple IPhone users in Surabaya. This type of research uses descriptive causal using data management from SPSS and SmartPLS. The results of this study indicate that the direct influence of brand experience on brand loyalty has no significant effect, while indirect influence on brand experience on brand loyalty through affective commitment has a significant influence